Amelogenesis imperfecta: A challenge to restoring esthetics and function - Ranganath V; Nichani Ashish; Soumya V (Wolters Kluwer Medknow Publications, 2010)
Rehabilitation of complicated cases poses difficulty in clinical practice, both with respect to restoring function and with esthetics. One such clinical condition where the dentist has to give importance to proper planning of the treatment and execution of the plan is amelogenesis imperfecta (AI), a condition where both function and esthetics are accommodated. This article discusses both the functional and esthetic rehabilitation of a patient with AI. Both the esthetics and function were hampered in this patient due to the condition. As a result, the treatment was properly planned and executed. A number of treatment options are available for us today to treat such a case. There is no one technique to be followed as such. However, the aim was to properly diagnose the case and provide good function and esthetics to the patient.